Faster carbon turnover in topsoil with straw addition is less beneficial to carbon sequestration than subsoil and mixed soil. Issue 6 (21st July 2022) - Dai, Shan‐Shan; He, Peng; Guo, Xiao‐Li; Ge, Tida; Oliver, Margaret A.; Li, Lu‐Jun
Abstract: In arable soils, the topsoil and subsoil are commonly mixed in the operation of deep tillage. It is not yet clear whether the influence of crop straw on soil organic matter (SOM) mineralization of the mixed soil (from the topsoil and subsoil) is different from that of solely the topsoil or subsoil. We conducted a 120‐d incubation experiment with the addition of 13 C‐labeled maize ( Zea mays L.) straw to study SOM mineralization and straw decomposition in the topsoil (0–15 cm), subsoil (15–30 cm), and their mixture (0–30 cm). Straw addition promoted SOM mineralization and thus induced a positive priming effect. The mineralization of SOM in topsoil with straw addition was 122% higher than in subsoil, and 45% higher than in mixed soil. After the 120‐d incubation, 12–16% of straw C was mineralized as CO2, contributing approximately 50–70% to the total CO2 production. Furthermore, straw C was also incorporated into SOM fractions, with 34, 7, and 59% in the light fraction, particulate organic C (coarse and fine), and mineral‐associated organic C (MAOC) in topsoil, respectively. The SOM mineralization and priming were greater in the topsoil with higher dissolved organic C and NO3 –N throughout the incubation. Despite more straw C retained in MAOC in topsoil, the significant decrease in total MAOC with straw addition indicated that SOM turnover induced by fresh C application was probably faster in topsoil than the subsoil and mixed soil. Our findings indicated that both subsoil and mixed soil tended to sequester C with straw addition, whereas topsoil C turnover was faster than subsoil in the presence of straw addition. Core Ideas: SOM mineralization of mixed soil from topsoil and subsoil was quantified. Residue C retained in SOC fractions was also determined. Mixed topsoil and subsoil resulted in an additive effect on the SOM priming. Higher SOC priming and turnover was observed in the topsoil than subsoil.